The culmination of multidrug-resistant efflux pumps vs. meager antibiotic arsenal era: Urgent need for an improved new generation of EPIs - Chetri, Shiela (Frontiers in Microbiology, 2023)
Efflux pumps function as an advanced defense system against antimicrobials by reducing the concentration of drugs inside the bacteria and extruding the substances outside. Various extraneous substances, including antimicrobials, toxic heavy metals, dyes, and detergents, have been removed by this protective barrier composed of diverse transporter proteins found in between the cell membrane and the periplasm within the bacterial cell. In this review, multiple efflux pump families have been analytically and widely outlined, and their potential applications have been discussed in detail. Additionally, this review also discusses a variety of biological functions of efflux pumps, including their role in the formation of biofilms, quorum sensing, their survivability, and the virulence in bacteria, and the genes/proteins associated with efflux pumps have also been explored for their potential relevance to antimicrobial resistance and antibiotic residue detection. A final discussion centers around efflux pump inhibitors, particularly those derived from plants.